Prevalence of Overweight and Obesity among Adolescents in Seven Arab Countries: A Cross-Cultural Study - Abdulrahman O. Musaiger; Mariam Al-Mannai; Reema Tayyem; Osama Al-Lalla; Essa Y. H. Ali; Faiza Kalam; Mofida M. Benhamed; Sabri Saghir; Ismail Halahleh; Zahra Djoudi; Manel Chirane (Hindawi Limited, 2012)
Objective. The aim of this study was to find out the prevalence of overweight and obesity among adolescents in seven Arab countries using similar reference standard. Methods. A school-based cross-sectional study was carried out in seven cities in Arab countries, namely, Algeria, Jordan, Kuwait, Libya, Palestine, Syria, and United Arab Emirates. A multistage stratified random sampling technique was used. The total sample included was 4698 adolescents aged from 15 to 18 years (2240 males, 2458 females). The International Obesity Task Force (IOTF) reference standard was used to classify the adolescents as nonobese, overweight, and obese. Results. Among males, overweight was highest among Kuwaiti adolescents (25.6%), followed by Jordanian (21.6%), and Syrian (19.7%) adolescents. Among females, the highest prevalence of overweight was reported in Libyan adolescents (26.6%), followed by Kuwaiti (20.8%), and Syrian (19.7%) adolescents. As for obesity, Kuwaiti adolescents showed the highest prevalence of obesity for both males (34.8%) and females (20.6%). Conclusion. There is an urgent need to establish a plan of action to combat obesity in schoolchildren in these countries.